From Thousand Canals to Roads: The Transformation of Transportation Mode in Pontianak - Ivan Gunawan; Bambang Soemardiono; Dewi Septanti (Journal of Regional and City Planning, 2023)
Pontianak City was established in 1771 on the the Kapuas River and Landak River riverbanks, the latter being the longest river in Indonesia. The city was once known as the City of a Thousand Canals. However, in its development, people shifted to land transportation modes, leaving the canals in an extinction process. This study aimed to uncover the factors and impacts of the inland water transportation network fading from the Pontianak urban structure. The research used a sequential explanatory design, combining qualitative methods in the form of literature review and quantitative methods using space syntax analysis. By comparing the spatial configuration of the canals and roads in a diachronic approach, the study found proof of the importance of the canals’ existence in the Pontianak urban structure. Water transportation can be the answer to fixing environmental issues, flood hazards, and traffic congestion. Revitalizing the canals can help bring a healthy water environment because the people will change their perception of the canals from sewage routes to transportation routes. Revitalizing the canals can also bring back waterside activity, generate a sense of belonging, and bring back part of the former identity of Pontianak City.